A Case Control Study on the Incidence and Prevalence of Hip Fracture in Association with Hypoglycemic Drugs Among Type II Diabetic Patients in a Major Trauma Care Center - T V, Aishwarya; Sunny, Aleena; Sunny, Aleena; Biji, Priya; Duraisingh L, Britto; KP, Mohanraj; T, Sivakumar (Indian Journal of Pharmacy Practice)
Background: Type II DM is a common metabolic disorder with increasing prevalence throughout the world. There is growing evidence indicating the effects of medications for diabetes on bone metabolism and fracture risk. More research is required to know the overall impact of these medications on bone health. Aim: To determine the incidence and prevalence of hip fracture in association with hypoglycemic drugs among Type II DM patients in major trauma care center. Objectives: To evaluate and compare the incidence and prevalence of hip fracture, the effect of hypoglycemic drugs on bone metabolism and fracture risk as well as the future probability of hip fracture risk in diabetes patients taking hypoglycemic drugs. Methodology: A case-control study was conducted with a sample size of 250 patients which included 95 cases and 155 control subjects enrolled for a period of 6 months in a major trauma care center. Subjects were assessed for future hip fracture risk within 10 years using WHO FRAX Score. Odds ratio (OR) were calculated using Fisher’s Exact Test and statistical testing was performed at 0.05% level of significance with 95% CI. Results: Type II DM patients taking hypoglycemic drugs were associated with increased risk of hip fracture (odds ratio [OR] =2.97). Incidence (19.2%) and prevalence (60%) of hip fractures was higher in patients taking hypoglycemic drugs than the incidence (14.8%) and prevalence (40%) of those who were not taking the drug. Conclusion: Hip fracture incidence in Type II DM patients taking hypoglycemic drug is higher than the patients who were not taking the drugs. FRAX tool has been proved to be helpful in preventing future incidents.
Keywords: Type II DM; Hypoglycemic; Incidence; Prevalence; Hip fracture.